(untitled) (IJM: Journal of Multidisiplinary, 2025)
This study aims to find empirical evidence regarding the factors that influence the assessment and measurement tools of financial performance in manufacturing companies listed on the Indonesia Stock Exchange. The factors tested in this study are liquidity and solvency in relation to financial performance. The sample used in this study consists of 80 manufacturing companies listed on the Indonesia Stock Exchange from the period of 2019 to 2022. The research method uses a quantitative approach and purposive sampling for sample selection. Hypothesis testing is conducted using linear regression. The results of this study show that the Solvency Ratio (X1) has a significant effect on financial performance, as indicated by the t-table value (3.329 > 1.99085) and a significant value of (0.001 < 0.05). The Liquidity Ratio (X2) overall shows no significant effect on the company's financial performance, as seen from the table showing (2.073 > 1.99085) and a significance value of (0.041 < 0.05). Both variables, when tested simultaneously, have an impact on financial performance, as the calculated F-value is greater than the F-table value (5.589 > 3.11) with a significance value of 0.005, which is lower than the standard value of 0.05.